2008
DOI: 10.1089/jop.2007.0117
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Study of Dexamethasone Disodium Phosphate using Intravitreal, Subconjunctival, and Intravenous Delivery Routes in Rabbits

Abstract: Dexamethasone is a corticosteroid with proven efficacy for treating both anterior- and posterior-segment ocular diseases. Delivery of drugs to the back of the eye has always been a challenge, with dexamethasone being no exception. There are multiple delivery routes to the retina, with each exhibiting different pharmacokinetics, depending on the drug molecule and specific route of administration. In this study, we used intravenous (IV), subconjunctival (SC), and intravitreal (IVT) injections in rabbits to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…SC injection of DSP solution has been shown to more effectively deliver high levels of DSP to both the aqueous and vitreous as compared to eye drops [17,18]. It is noteworthy that we found that SC administration of free DSP resulted in more than 8-fold higher systemic DSP concentration compared to SC injection of DSP-NP at PO 2 h. Due to the sustained release of DSP, systemic exposure to DSP was minimal (50 ng/mL) over 7 days after SC administration of DSP-NP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SC injection of DSP solution has been shown to more effectively deliver high levels of DSP to both the aqueous and vitreous as compared to eye drops [17,18]. It is noteworthy that we found that SC administration of free DSP resulted in more than 8-fold higher systemic DSP concentration compared to SC injection of DSP-NP at PO 2 h. Due to the sustained release of DSP, systemic exposure to DSP was minimal (50 ng/mL) over 7 days after SC administration of DSP-NP.…”
Section: Discussionmentioning
confidence: 99%
“…SC injection of dexamethasone sodium phosphate (DSP) solution has been shown to result in increased concentrations of DSP in the aqueous humor compared to drug concentrations achieved with eye drops [17,18]. However, rapid clearance of small molecules like DSP from the ocular tissue limits the duration of therapeutic drug levels after a single SC injection, and the spike in drug concentration may cause increased ocular side effects.…”
Section: Introductionmentioning
confidence: 99%
“…The limit of detection was 100 g/L. Two LC-MS/MS methods have been reported for the simultaneous determination of Dex and Dex SP in plasma or connective tissue for pharmacokinetics studies [8,9]. The method for plasma [8] required 100 l of plasma, and protein precipitation by acetonitrile was used for sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…The method for plasma [8] required 100 l of plasma, and protein precipitation by acetonitrile was used for sample preparation. The method for connective tissue [9] required 50 mg of tissue, which was homogenized with water. After centrifugation, the supernatant was filtered and the filtrate was injected into LC-MS/MS.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, few comprehensive studies have been published on drug pharmacokinetics and eye tissue distribution following SCJ injections (stability, retention time, rate of elimination, drug concentration at the target tissue). [6][7][8][9] These parameters are likely to be drug specific or target specific.…”
mentioning
confidence: 99%